Risk Factor Associated with Recurrence after OM-89 (Uro-Vaxom®) Treatment for Female Recurrent Cystitis - Han, Ji-Yeon (Urogenital tract infection, 2019)
Purpose: This study evaluated the risk factors associated with recurrence OM-89 (Uro-Vaxom®) treatment for female recurrent cystitis.Materials and Methods: The medical records of patients who received OM-89 for at least six months were reviewed retrospectively. Patients were excluded from the analysis if they had an abnormal lower urinary tract anatomy, residual urine volume ≥200 ml, a history of genitourinary tuberculosis, urological cancer or pelvic radiation, indwelling urinary catheter, or had genitourinary surgery within the previous six months. Patients were categorized into two groups: (1) no recurrence and (2) recurrent cystitis after OM-89. The risk factors in the two groups were compared. The recurrent cystitis was defined as two more infections in six months or three or more in one year.Results: A total of 52 female were included. Group 1 had 35 (67.3%) patients and group 2 had 17 (32.7%) patients. Before and after the OM-89, the mean cystitis episodes for six months of groups 1 and 2 were 4.19±4.60 (range, 2-24) and 1.17±1.79 (range, 0-6), respectively, which were decreased significantly (p＜0.001). For recurrence after the OM-89, the only risk factor was uncontrolled diabetes (fasting plasma glucose level ＞120 mg/dl±casual plasma glucose ＞180 mg/dl) (p=0.002). No significant differences in the age, menopause, daily water intake, hormone replacement therapy or history of extended-spectrum beta-lacta-mase-producing Escherichia coli were observed between the two groups.Conclusions: OM-89 was effective in the management of recurrent cystitis in female. On the other hand, uncontrolled diabetes was a risk factor for treatment failure of OM-89. KCI Citation Count: 0